Socio-Cultural Potential for Low Delivery Assistance by Nakes in Working Area of the Bibida Health Center, Paniai Regency, Central Papua - Amir, Aprima Yona; Sari, Silvie Permata; Rozyka, Fafelia; Herayono, Febby (PT. Riset Press International, 2024)
One method that can reduce maternal and newborn mortality rates is delivery carried out by health workers. Most maternal and newborn complications and deaths occur during the labor period. This happens because the assistance is provided by health workers who do not have midwifery (professional) competence. This study aims to identify factors that contribute to the low level of delivery assistance by health workers in the Bibida Community Health Center working area. In 2021, 56.3 percent of births will be assisted by health workers, and 32% will be at the Bibida Community Health Center. Quantitative research was conducted using a cross-sectional analytical design. The research was conducted in the Bibida Community Health Center working area in Paniai Regency, Central Papua, from October 2023 to November 2023. This research involved all mothers who had just given birth who were in the Bibida Community Health Center working area during July, August and September. The total population technique was used to collect 35 samples. Use of computerization to process univariate and bivariate data. Research resultdelivery assistance by non-health workers 62.9% andculture does not support 51.4%. With p value=0.000, the results of statistical analysis show that there is a socio-cultural relationship. It is recommended that pregnant women give birth at health workers and in health facilities. In addition, it is important for midwives to work together with local community leaders and related sectors in encouraging people to give birth with health workers.